Higher level learning outcomes attained through assessment - Maria Antónia Carravilla (2012)
Bloom's taxonomy for learning domains proposes six categories for the cognitive domain, that go from the basic remembering of facts and definitions to the complex creation act, in which new knowledge structures or patterns are built or new meanings assigned. The Bologna Declaration strained the emphasis on the learning outcomes and on their alignment with the assessment. In this paper a step forward is proposed, in which the assessment process itself has a central role in the attainment of the learning outcomes. A case study of the Operations Research course, involving 350 students from 4 different engineering degrees, is described and conclusions drawn about the effectiveness of this assessment organization in the students development of the higher level learning outcomes of Bloom's taxonomy.